Lumbar spinal angiolipoma: case report and review of the literature - (:unkn) unknown (SPRINGER, 2006)
Spinal angiolipomas are extremely rare benign tumors composed of mature lipomatous and angiomatous elements. Most are symptomatic due to progressive spinal cord or root compression. This article describes the case of a 60-year-old woman who presented with a 6-month history of low back pain radiating to her right leg. The pain was multisegmental. The condition had worsened with time. Lumbar magnetic resonance imaging revealed a dorsal epidural mass at L5 and erosion of the lamina of the L5 vertebra. Laminectomy was performed, and an extradural tumor was totally excised. Neuropathologic examination identified it as a lumbar spinal angiolipoma. There was no evidence of recurrence in follow-up 12 months later. This rare clinical entity must be considered in the differential diagnosis for any spinal epidural lesion.
Keywords: angiolipoma; spinal tumor; INFILTRATING ANGIOLIPOMA; EPIDURAL ANGIOLIPOMA; LIPOMA